Factors influencing desired family size among women of childbearing age in eastern Indonesia: Evidence from the Indonesian Demographic Health Survey - Cindy Ade Aulia; Siti Nurrochmah; Lucky Radita Alma; Supriyadi Supriyadi (Public Health and Occupational Safety Journal)
Background: Globally, Indonesia is the fourth most populous country. Based on the results of the Indonesian Central Bureau of Statistics census, it is known that the population of Indonesia in 2017 was around 261 million people, with an average number of children desired by women of childbearing age in East Nusa Tenggara Province of 2.9 or around three children per woman of childbearing age.